Odprta (državljanska) znanost - Adam, Frane (Družboslovne razprave, 2024)
The article discusses the significance of open science, notably the concept of citizen science, within a broader sociopolitical and socio-scientific context. The authors point out the ambivalence of these concepts and the lack of critical reflection on possible negative implications. They argue that while open and citizen science can benefit researchers and cognitively active citizens by enriching knowledge and fostering opportunities for social innovation, there are risks and unintended consequences that may influence scientific autonomy. The authors caution against the illusion that ad hoc citizen science projects bring exceptional, immediate results, warning that the open science movement could be used to divert attention from more pressing issues and anomalies within the scientific domain
Keywords: državljanska znanost; odprta znanost; scientifikacija družbe; socializacija znanosti; znanstvena politika